Land and Water Carrying Capacity in Tourism Area of Nusa Penida, Bali (International Journal of Scientific Research and Management (IJSRM), 2020)
Environmental resources are very important in supporting tourism activities. As a developing tourism area Nusa Penida needs sufficient land and water resources. Increasing population of residents and tourists triggers new activities that affect the patterns of land use and available water, which in turn has a negative impact on the availability of land and water. The carrying capacity of the environment is disrupted due to the utilization of environmental resources that exceed its capacity. This study aims to calculate the availability, needs and status of the carrying capacity of land and water in the Nusa Penida Tourism Area.The methodology of this study is to calculate the availability of land and water, calculate land and water needs for residents and tourists and calculate the carrying capacity of land and water. This study predicts the availability of land and water, land and water needs and the carrying capacity of land and water in the Nusa Penida Tourism Area until 2023.From the results of data analysis shows that the availability of land in Nusa Penida amounted to 5,350 hectares. Projected land needs until the year 2028 of 24,640 hectares, the carrying capacity of the land in Nusa Penida deficit. The results of the calculation of land requirements based on the ecological footprint amounted to 17,724.283 hectares, while the availability of land in Nusa Penida was 5,350 hectares. This shows that the carrying capacity of the land in Nusa Penida has a deficit of 12,374,283 hectares. Availability of water based on rainfall and springs in Nusa Penida is 95,443,402.56 m3/year. The results of data analysis show that in 2028 water needs for residents and tourists are estimated at 83,398,400 m3/year. Projection of the carrying capacity of water in Nusa Penida based on rainfall surplus of 901,002.56 m3/year. Projection of the carrying capacity of water in Nusa Penida based 10% utilization of springs Penida and Guyangan in 2028 surplus of 2,433,865,856.44 m3/year Projection of the carrying capacity of water in Nusa Penida based on rainfall + 10% utilization of springs Penida and Guyangan in 2023 surplus of 2,529,309,259 m3/year. Projection of the carrying capacity of water in Nusa Penida based on rainfall + all springs water potencyin Nusa Penida in 2028 surplus of 34,958,390,240 m3/year.